ChemInform Abstract: 3‐(Dimethylamino)‐1‐propylamine: A Cheap and Versatile Reagent for Removal of Byproducts in Carbohydrate Chemistry. Issue 28 (July 2015) - Andersen, Sofie Meng; Heuckendorff, Mads; Jensen, Henrik H.
Abstract 3‐(dimethylamino)‐1‐propylamine is used as reagent for selective anomeric deacylation in carbohydrate chemistry to give 1‐O deprotected sugars in high yields without chromatographic purification.